Advances in the application of bone turnover markers for pediatric growth and developmental disorders: a review - Wang, Yuxin; Hu, Honghua; Huang, Yi (Frontiers in Endocrinology, 2025)
Bone turnover markers (BTMs) are biomedical indicators used to assess the bone metabolism processes reflecting the activity of osteoblasts and osteoclasts. During childhood and adolescence, bone metabolism is highly active, leading to distinct levels and trends of BTMs compared with those of adults. BTMs correlate significantly with age, gender and environmental factors, making them valuable for evaluating bone health and developmental trajectories in pediatric populations. Due to the non-invasive characters and dynamic monitoring capabilities, BTMs are increasingly employed in research and clinical practice. Preliminary observations propose that BTMs demonstrate clinical utility in predicting fracture risk, enabling early diagnosis of osteoporosis and rickets, and monitoring therapeutic efficacy. However, Tracability of BTM measurement results and limited pediatric reference intervals remain critical challenges. Further research is needed to expand our understanding of the their mechanisms and optimize clinical applications. This article reviews the physiological and pathological states in children, discusses the current dilemmas of clinical application, and highlights the future research prospects.